The Role and Application of Exosomes in Gastric and Colorectal Cancer - Li, Qirong; Wang, Dongxu; Ding, Dayong; Feng, Ye; Hou, Ruizhi; Liu, Dianfeng; Lin, Chao; Gao, Yongjian (Frontiers in Pharmacology, 2022)
Gastric cancer and colorectal cancer are malignant tumors found in the human gastrointestinal tract. The bidirectional communication between tumor cells and their microenvironment can be realized through the transmission of exosomes – small, cell-derived vesicles containing complex RNA and proteins. Exosomes play an important role in the proliferation, metastasis, immune response, and drug resistance of cancer cells. In this review, we focus on the role and application of exosomes in gastric and colorectal cancer. We also summarize the role of exosomes secreted by different types of cells in tumor development and as drug carriers in cancer treatment.